Poverty, Material Hardship, and Children's Outcomes: A Nuanced Understanding of Material Hardship in Childhood - Anika Schenck-Fontaine; Rebecca M. Ryan (MDPI AG, 2022)
There are four distinct, related types of material hardship-basic expense hardship, food insecurity, housing hardship, and medical hardship. Extant research has not sufficiently accounted for the complex relationships between these different types of material hardship. Using 1997 and 2002 data from the Panel Study of Income Dynamics Child Development Study on a national sample of 3- to 17-year-old children (N = 3563), this study describes the prevalence of each type of material hardship, their relative correlations, and their associations with children's behavior problems, and reading and math scores. Material hardship is more prevalent than income poverty and the four types of material hardship were only moderately correlated with each other. Only basic expense hardship, food security, and one type of medical hardship were associated with increased behavior problems. Only housing hardship was associated with lower math and reading scores. These findings highlight the need to more carefully investigate the distinctions between material hardship types in childhood and the importance of a diversified set of policy responses to protect children from the possible effects of distinct, but interrelated experiences of material hardship.